2019
DOI: 10.1007/s00125-019-4933-y
|View full text |Cite
|
Sign up to set email alerts
|

Outcomes of people with severe hypoglycaemia requiring prehospital emergency medical services management: a prospective study

Abstract: Aims/hypothesis The aim of this work was to investigate clinical outcomes following severe hypoglycaemia requiring prehospital emergency medical services (EMS) management. Methods We carried out a prospective, observational study of adults with diabetes attended by prehospital EMS for management of severe hypoglycaemia between April 2016 and July 2017. Information on precipitants, hospitalisation, length of hospital stay and recurrence was collected at 1 and 3 months following the episode of severe hypoglycaem… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
6
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(8 citation statements)
references
References 33 publications
2
6
0
Order By: Relevance
“…This level of use is comparable to that documented nearly 20 years ago in Germany, where 5 % of patients who presented to hospitals with severe hypoglycaemia received glucagon [19]. Data from other countries vary: a recent prospective, observational study conducted in Australia documented use of glucagon in 5.7 % of patients with severe hypoglycaemia who were treated by prehospital emergency medical services [40] and a 2014 report from Italy found that 1.2 % of patients received glucagon from out-of-hospital emergency services personnel [8]. Other staff at clinical office 2 0 1 0…”
Section: Discussionsupporting
confidence: 75%
“…This level of use is comparable to that documented nearly 20 years ago in Germany, where 5 % of patients who presented to hospitals with severe hypoglycaemia received glucagon [19]. Data from other countries vary: a recent prospective, observational study conducted in Australia documented use of glucagon in 5.7 % of patients with severe hypoglycaemia who were treated by prehospital emergency medical services [40] and a 2014 report from Italy found that 1.2 % of patients received glucagon from out-of-hospital emergency services personnel [8]. Other staff at clinical office 2 0 1 0…”
Section: Discussionsupporting
confidence: 75%
“…Earlier data from Germany recorded that SH comprised 3% of the total out-of-hospital EMS annual caseload 20 , which is consistent with international figures of 1–4% 12 23 . Currently, only 6% of German emergency physicians have reported that SH had increased in frequency during the last 3–5 years, whereas 13% thought there had been a decrease and 82% considered that there has been no change.…”
Section: Discussionsupporting
confidence: 80%
“…The pre-conditions for treatment of an SH event without the necessity for hospital admission, are an uncomplicated event in patients who are known to be well educated about the self-management of their diabetes (93 %) and about the use of insulin therapy (44 %). Prospective studies from Germany [21] and Australia [12] in addition to retrospective data from Denmark [22] confirmed the safety of treating SH without hospitalisation in cohorts of selected patients with diabetes. However, in 2020 only a few (11 %) German emergency physicians reported that sulfonylurea-treated patients and older patients with multiple co-morbidities were treated without subsequent hospital admission, a practice that is unchanged from 2001 (9 %).…”
Section: Discussionmentioning
confidence: 82%
“…Reattendance for recurrent hypoglycaemia is also common, affecting 5% within 48 h [ 20 ] and 10% within 3 months [ 21 ]. Current UK guidelines for ambulance services have advocated communicating with primary care or diabetes nurse teams following an episode of hypoglycaemia [ 22 ] but despite this recommendation, follow-up, therapy change or specialist intervention in people self-reporting severe hypoglycaemia are uncommon, suggesting that care pathways are poorly developed or not used [ 21 , 23 ].…”
Section: Discussionmentioning
confidence: 99%